Legal Relationship and Rights Fulfillment of Salt Pond Workers / Laborers in Sumenep Regency - R, Risqi Septia Ananda; Lutfillah; Dawairoh; Fatoni, Syamsul (VJJ, 2021)
Sumenep Regency has thousands of hectares of land used as salt ponds. Therefore, many people in Sumenep make a living as salt farmers. The salting process is carried out by salt farmers independently or in groups, also by PT Garam. The status of salt farmers is seen from the number of Madura salt production actors consisting of owner farmers and sharecroppers or mantong. There is an interaction between parties which may consist of landowners and salt farmers/mantong as well as workers/laborers who work at PT. Garam forms a legal relationship. In this legal relationship, there are differences in the systems used by the parties, such as employment relationships and partnership relationships, so this becomes an ambiguity regarding the status and rights of the workers. This article explores the following research questions: how is the legal relationship between salt pond workers in Sumenep Regency and have the rights of salt pond workers in Sumenep Regency been fulfilled? The purpose of this study is to find out the legal relationship of salt pond workers in Sumenep Regency and to find out whether the rights of salt pond workers in Sumenep Regency were fulfilled. The research type is empirical research and the approach used was empirical juridical. The results of this study are the effectiveness of statutory policies regarding clarity of worker status and the fulfillment of the rights of salt pond workers.